Estymatory miar Expected Shortfall i Value at Risk : przykłady zastosowania do pomiaru ryzyka walutowego - Olbryś, Joanna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Concept of Value at Risk appears in 1994. Nowadays VaR is the most popular risk measure. Unfortunately, it fails to reward diversification, as it is not subadditive. In the search for a suitable alternative to VaR, Expected Shortfall (ES) has been characterized as the smallest coherent risk measure to dominate VaR. The aim of this paper i san application of Expected Shortfall and Value-at-Risk estimators to risk estimate examples on the Polish currency market. The paper also offers a comparison of ES and VaR as risk measures. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 65-72